Characterization of a Cell-Assembled extracellular Matrix and the effect of the devitalization process. (December 2018) - Magnan, Laure; Labrunie, Gaëlle; Marais, Sébastien; Rey, Sylvie; Dusserre, Nathalie; Bonneu, Marc; Lacomme, Sabrina; Gontier, Etienne; L'Heureux, Nicolas
Graphical abstract: Abstract: We have previously shown that the Cell-Assembled extracellular Matrix (CAM) synthesized by normal, human, skin fibroblasts in vitro can be assembled in a completely biological vascular graft that was successfully tested in the clinic. The goal of this study was to perform a detailed analysis of the composition and the organization of this truly bio-material. In addition, we investigated whether the devitalization process (dehydration) used to store the CAM, and thus, make the material available "off-the-shelf, " could negatively affect its organization and mechanical properties. We demonstrated that neither the thickness nor the mechanical strength of CAM sheets were significantly changed by the dehydration/freezing/rehydration cycle. The identification of over 50 extracellular matrix proteins highlighted the complex composition of the CAM. Histology showed intense collagen and glycosaminoglycan staining throughout the CAM sheet. The distribution of collagen I, collagen VI, thrombospondin-1, fibronectin-1, fibrillin-1, biglycan, decorin, lumican and versican showed various patterns that were not affected by the devitalization process. Transmission electron microscopy analysis revealed that the remarkably dense collagen network was oriented in the plane of the sheet and that neither fibril density nor diameter was changed by devitalization. Second harmonic generation microscopy revealed an intricate, multi-scale, native-like collagen fiber orientation. In conclusion, this bio-material displayed many tissue-like properties that could support normal cell-ECM interactions and allow implantation without triggering degradative responses from the host's innate immune system. This is consistent with its success in vivo . In addition, the CAM can be devitalized without affecting its mechanical or unique biological architecture. Statement of Significance: The extracellular matrix (ECM) defines biological function and mechanical properties of tissues and organs. A number of promising tissue engineering approaches have used processed ECM from cadaver/animal tissues or cell-assembled ECM in vitro combined with scaffolds. We have shown the clinical potential of a scaffold-free approach based on an entirely biological material produced by human cells in culture without chemical processing. Here, we perform a comprehensive analysis of the properties of what can truly be called a bio-material. We also demonstrate that this material can be stored dried without losing its remarkable biological architecture.